Effects of Moderate-Intensity Resistance Exercise on Blood Pressure in Hypertensive Individuals - Marya Rahmani Ghobadi; Rastegar Hoseini; Zahra Hoseini (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2016)
The purpose of this study was to evaluate the effects of moderate-intensity resistance exercise on postexercise hypotension (PEH) in the hypertensive. The study was conducted with eighteen hypertensive elderly individuals (20–30 years). They were subjected to two experimental sessions: control session (SC) and 50% (S50%) of 1RM. For each session, subjects were evaluated pre-and postintervention. In the preintervention, the blood pressure (BP) and FVR were measured after 10 min of rest. Thereafter, they were taken to the gym to perform the exercise sessions or remained at rest in each of the equipment during the same time.In the S50% group was composed of a set of ten repetitions of ten exercises, with an interval of 90 s between exercises. Subsequently,the FVR and BP measurements were again performed at 15, 30, 45, 60 and 75 min of recovery (postintervention). The PEH was greater in S50% compared with SC, with the lower value of BP being found at 75 min of recovery for the two sessions (systolic BP:125.21 ±0.98mmHg versus 145.45 ±1.72 mmHg; diastolic BP: 83.60 ±1.67 mmHg versus 95.14 ±0.74 mmHg respectively). Moderateintensity resistance exercise was effective in promoting PEH, this phenomenon being accompanied by a reduction in FVR within the first minute of recovery in the hypertensive young.